THE ROLE OF PRONUNCIATION IN EFFECTIVE ENGLISH COMMUNICATION - Bobomurodova Mokhinur Bakhriddin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Pronunciation plays a critical role in effective English communication, acting as a bridge between speakers and listeners. This paper explores the significant role that pronunciation plays in enhancing communication skills in English, particularly in spoken interactions. The study investigates various aspects of pronunciation such as accent, stress, and intonation, and discusses how mastering these elements can lead to clearer and more confident communication. The goal is to highlight the importance of pronunciation in overcoming barriers to understanding and facilitating smoother interactions in both formal and informal contexts. The paper provides a comprehensive overview of the challenges learners face in pronunciation and offers strategies to overcome them, promoting a holistic approach to language acquisition.